Inter-system handoff management in mobile cellular networks / Syamil Khalid - Khalid, Syamil (2011)
This paper presents a handoff technique or handoff management which supports the mobility between dissimilar networks or service providers especially in Global System of Communication Mobile (GSM) technology. The boundary cell of cellular network system is also designed by using MATLAB R2009a software. A simulation model developed to study the performance of the relative signal strength with hysteresis and threshold (RSS-HT) algorithm between mobile and radio tower in cellular network. The theoretical analysis and simulation result are studied to evaluate the handoff parameters and signal strength of mobility.